Association of low blood pressure with suicidal ideation: a cross-sectional study of 10,708 adults with normal or low blood pressure in Korea - Kyung-in Joung; Sung-il Cho (BMC, 2018)
Abstract Background Whether constitutional low blood pressure (BP) causes substantive health problems has been controversial, and subjects with hypotension exhibit a range of symptoms, from mild typical conditions such as tiredness and dizziness to more specific psychological conditions and even cognitive disorders. This study investigated whether low BP is associated with suicidal ideation in the general population. Methods Four years of data from the 2010-2013 Korean National Health and Nutrition Examination Survey were used. Among the 23,163 participants, aged 19-101 years, 10,708 with normal or low BP were included in the analysis of the association between low BP and suicidal ideation. The criterion used for low BP was systolic BP (SBP) < 100 mmHg, and in comparative analyses, the criteria used for low BP were SBP < 110, < 95, and < 90 mmHg. The association of prehypertension or hypertension with suicidal ideation was also examined. Suicidal ideation was assessed by a questionnaire. Results Compared with the normotensive reference group, the odds ratios (ORs) for suicidal ideation were significantly higher in the three hypotensive groups after adjusting for sex, age, body mass index, total cholesterol level, household income, educational level, marital status, current smoking status, alcohol intake, and the interaction between sex and age (OR = 1.29, 95% confidence interval [CI], 1.08 to 1.55; OR = 1.44, 95% CI, 1.14 to 1.82; and OR = 1.71, 95% CI, 1.11 to 2.62 for SBP < 100, SBP < 95, and SBP < 90 mmHg, respectively). Adding the clinical morbidities of diabetes mellitus, stroke, myocardial infarction/angina pectoris, and depression as covariates had little effect on the strength of the associations (OR = 1.25, 95% CI, 1.04 to 1.50; OR = 1.43, 95% CI, 1.13 to 1.81; and OR = 1.74, 95% CI, 1.14 to 2.68 for SBP < 100, < 95, and < 90 mmHg, respectively). Conclusions Low SBP showed an association with suicidal ideation in the general Korean population. The association was significant for low BP, defined as a SBP < 100 mmHg, and the strength of the association increased as the criteria for low BP increased in strictness.